2022
DOI: 10.1371/journal.pone.0279229
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ultrasound-based antenatal screening strategies to detect vasa praevia in the United Kingdom: An exploratory study using decision analytic modelling methods

Abstract: The objective of this exploratory modelling study was to estimate the effects of second-trimester, ultrasound-based antenatal detection strategies for vasa praevia (VP) in a hypothetical cohort of pregnant women. For this, a decision-analytic tree model was developed covering four discrete detection pathways/strategies: no screening; screening targeted at women undergoing in-vitro fertilisation (IVF); screening targeted at women with low-lying placentas (LLP); screening targeted at women with velamentous cord … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…3 A recent article comparing different screening strategies found that screening based on low-lying placenta may be superior to screening based on presence of velamentous cord insertion. 8 This case highlights the importance of follow-up ultrasound following a finding of low-lying placenta, and careful assessment of the vessels adjacent to the internal cervical os with TVS color Doppler. In this case, there was an arterial signal at the fetal heart rate, but type III cases with venous vasa previa can occur, making the diagnosis via ultrasound more nuanced.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…3 A recent article comparing different screening strategies found that screening based on low-lying placenta may be superior to screening based on presence of velamentous cord insertion. 8 This case highlights the importance of follow-up ultrasound following a finding of low-lying placenta, and careful assessment of the vessels adjacent to the internal cervical os with TVS color Doppler. In this case, there was an arterial signal at the fetal heart rate, but type III cases with venous vasa previa can occur, making the diagnosis via ultrasound more nuanced.…”
Section: Discussionmentioning
confidence: 81%
“…It has been suggested that type 3 vasa previa, while currently infrequently reported, may in fact be the most common type of vasa previa 3 . A recent article comparing different screening strategies found that screening based on low lying placenta may be superior to screening based on presence of velamentous cord insertion 8 . This article is protected by copyright.…”
Section: Discussionmentioning
confidence: 99%
“…Third-trimester assessment of the placenta is recommended if there is evidence that the lower placental edge reaches or overlaps the internal cervical os at the time of the routine anomaly scan 10 . Conversely, systematic screening for vasa previa or velamentous cord insertion is not recommended in the third trimester, in view of the technical difficulties and lack of robust evidence regarding its usefulness 31,32 .…”
Section: Placenta Accreta Spectrummentioning
confidence: 99%
“…However, the UK National Screening Committee continues to recommend not screening for vasa previa. 67 , 71 , 79 , 80 A recent modeling study from the United Kingdom has suggested that targeted screening of all patients with second-trimester placenta previas or low-lying placentas will detect about 60% of cases of vasa previa without leading to increased cost or modification of current protocols. 80 A recent opinion argued that vasa previa is more common than several conditions routinely screened for in pregnancy and, given the high detection rate of ultrasound screening and the dramatic difference in outcomes in prenatally diagnosed cases, advocated that there should be routine screening for vasa previa.…”
Section: Definition Clinical Presentation and Natural Historymentioning
confidence: 99%